Penerapan Model Project-Based Learning Untuk Meningkatkan Hasil Belajar Satuan Waktu Siswa Kelas III Sekolah Dasar - Ramadhanti, Nurkamillah; Sukmanasa, Elly; Imaniah, Riksa Suci (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
The purpose of this research is to improve learning outcomes of implementations of the Project Based Learning (PjBL) model. The research method used is collaborative classroom action research using Kemmis and M.c. Taggart model. Data collection techniques used were observation, test, and documentation. The research subjects were off class III-A with 20 students at SD Negeri Polisi 2 Bogor. The results of the research show that the success of applying the Project Based Learning (PjBL) model can improve student learning outcomes. This is evidenced by the learning completeness of classical in cycle I students reached 40% with an average value of 69.5. At the same time, the completeness of students learning outcomes classically in cycle II has increased to 90% in cycle II. The results of this study are expected to provide new knowledge about the influence of innovative and creative learning models, also can improve student learning outcomes.